1964
DOI: 10.2134/agronj1964.00021962005600060003x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Soil Temperature, Water Soluble Phosphorus in Applied Fertilizer, and Method of Placement to Growth of Winter Wheat1

Abstract: Synopsis Top growth total yield of P, and percentage of K in the tops were significantly lower while percentages of P and N were significantly higher in plants grown at 50° F. than in those grown at 60 or 70°. Applying phosphatic fertilizer in a zone, as compared to mixing it with the soil, increased top growth, P percentage in the tops, and total yield of P while it decreased the percentage of K in the tops. In general the amount of dry matter, percentage of P in tops, and total yield of P were increased as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Total nutrient uptake was not influenced by residue treatment (data not shown). Only total uptake of K was influenced by soil temperature, and was lower at the lower temperature, as noted by other investigators (2,9,13).…”
Section: Nutrient Concentrationsupporting
confidence: 80%
“…Total nutrient uptake was not influenced by residue treatment (data not shown). Only total uptake of K was influenced by soil temperature, and was lower at the lower temperature, as noted by other investigators (2,9,13).…”
Section: Nutrient Concentrationsupporting
confidence: 80%
“…The placement of phosphorus has been shown to increase the uptake of phosphorus (MacLeod et al 1975, Mulkey et al 1979) and the efficiency of phosphorus (Pearson andKirkham 1980, Peterson et al 1981). Placement of phosphorus has been reported to be most effective at low soil phosphorus levels (Fox andKang 1978, Peterson et al 1981), in dry soil conditions (Chaudhary and Prihar 1974, Ekeberg 1986), at low soil temperatures (Gingrich 1964, Power et al 1964, and with granular phosphorus fertilizer (Engelstad and Terman 1980). It is well established that potassium as a cation is absorbed to cation exchange surfaces and becomes available to plants from soil solution and by contact exchange.…”
Section: Broadcast Vs Placement Fertilizationmentioning
confidence: 99%
“…Placement of phosphorus has been reported to be most effective in soils with low phosphorus levels (Fox andKang 1978, Peterson et al 1981), in dry soil conditions (Chaud-hary andPrihar 1974, Ekeberg 1986), and at low soil temperatures (Gingrich 1964, Power et al 1964).…”
Section: Organically Cultivated Carrotsmentioning
confidence: 99%
“…A positive relationship between soil temperature and phosphorus uptake was observed in winter wheat (3). Mederski and Wilson (8) showed that the manganese content of soybeans was greater at high than at low soil temperature.…”
mentioning
confidence: 98%